Strategic Planning for Development of Micro Enterprises at the Department of Trade, Industry, Cooperatives, and Small and Medium Enterprises, Soppeng Regency - Guntur, Muhammad; Khumairah, Fatimah; Niswaty, Risma; Arhas, Sitti Hardiyanti (KnE Social Sciences, 2024)
MSMEs are businesses with a micro, small to medium production scale that can be owned by individuals or in the form of business entities of a certain type. In Indonesia, MSMEs are currently being worked on and continue to grow from year to year. This study aims to examine the strategic planning of micro-enterprise development in the Department of Trade, Industry, Cooperatives and Small and Medium Enterprises, Soppeng Regency. This type of research is descriptive qualitative. Data collection techniques were carried out by observation, interviews, and documentation. The data analysis technique used consists of data reduction, data display, and conclusion drawing. The results of the study show that Environmental Scanning (Environmental Analysis), in Soppeng Regency has abundant Natural Resources (SDA) which can be utilized by micro-entrepreneurs as a source of income by processing them into products that have sales value. Strategy formulation (Strategy Formulation), a strategic plan made by the PPK and UKM Office in accordance with the 2nd mission of the Regional Head, namely strengthening the realization of community welfare. Pay more attention to micro business actors so that they can prosper from the business they are involved in and develop. Strategy implementation (Implementation Strategy), the implementation of programs is inseparable from what has been stated in the strategic plan (renstra), but in implementing the programs researchers value it is still not optimal because of the lack of awareness of micro-entrepreneurs to register their business as fostered by the PPK Service and UKM. Evaluation and control (evaluation and supervision), evaluation of activities is carried out quarterly but for evaluation and supervision of micro business actors directly to the field the schedule is uncertain, this is due to the lack of funds to go directly to the field. Factors supporting the success of strategic planning are supported by the awareness of micro-entrepreneurs to register their businesses and complete all forms of licensing according to the type of business. The inhibiting factors for miscommunication between micro-entrepreneurs and the PPK and UKM Offices are that micro-business actors sometimes delay registering their businesses because they think that the management will be complicated and convoluted. Keywords: strategic planning, micro enterprises, department of trade, industry, cooperatives and small and medium enterprises